2012
DOI: 10.1099/mic.0.055640-0
|View full text |Cite
|
Sign up to set email alerts
|

A highly basic sequence at the N-terminal region is essential for targeting the DNA replication protein ORC1 to the nucleus in Leishmania donovani

Abstract: The conserved eukaryotic DNA replication protein ORC1 is one of the constituents of prereplication complexes that assemble at or very near origins prior to replication initiation. ORC1 has been shown to be constitutively nuclear in Leishmania major. This study investigates the sequences involved in nuclear localization of ORC1 in Leishmania donovani, the causative agent of visceral leishmaniasis. Nuclear localization signals (NLSs) have been reported in only a few Leishmania proteins. Functional analyses have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…LdORC1/CDC6 has an N-terminus sequence essential for its nuclear import. This signaling sequence comprises residues 2-5 (KRSR), among which K2, R3, and R5 are crucial for LdORC1/CDC6 proper localization (Kumar et al, 2012). Importantly, ChIP-chip approaches revealed that ORC1/CDC6 co-localizes with fired replication origins in T. brucei (Tiengwe et al, 2012a), supporting the hypothesis that ORC1/CDC6 is the functional counterpart of the ORC complex.…”
Section: Initiation Of Dna Replication and Prevention Of Rereplicationmentioning
confidence: 68%
See 3 more Smart Citations
“…LdORC1/CDC6 has an N-terminus sequence essential for its nuclear import. This signaling sequence comprises residues 2-5 (KRSR), among which K2, R3, and R5 are crucial for LdORC1/CDC6 proper localization (Kumar et al, 2012). Importantly, ChIP-chip approaches revealed that ORC1/CDC6 co-localizes with fired replication origins in T. brucei (Tiengwe et al, 2012a), supporting the hypothesis that ORC1/CDC6 is the functional counterpart of the ORC complex.…”
Section: Initiation Of Dna Replication and Prevention Of Rereplicationmentioning
confidence: 68%
“…Like in other protozoans, geminin homologous were not found in Trypanosomatidae (Table 1). Moreover, ORC1/CDC6 (Kumar et al, 2012), MCM2-7 (Dang & Li, 2011;Kumar et al, 2009;Minocha et al, 2011b), and GINS (Dang & Li, 2011) are expressed constitutively in the nucleus throughout the entire cell cycle, suggesting that the sub-localization of their respective complexes is not a regulative mechanism in these organisms. Interestingly, Li et al found that, in T. brucei, CDC45 is excluded from the nucleus after DNA replication (Dang & Li, 2011).…”
Section: Initiation Of Dna Replication and Prevention Of Rereplicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a few reports describe functional NLS in Leishmania [1922]. Due to this, it is not possible to find a common sequence for nuclear transport in these parasites.…”
Section: Introductionmentioning
confidence: 99%